Baclofen blocks the acquisition and expression of mitragynine-induced conditioned place preference in rats - Yusoff, Nurul H. M.; Mansor, Sharif M.; Müller, Christian P.; Hassan, Zurina (Behavioural Brain Research, 2018)
Mitragynine is the major alkaloid found in the leaves of M. speciosa Korth (Rubiaceae), a plant that is native to Southeast Asia. This compound has been used, either traditionally or recreationally, due to its psychostimulant and opioid-like effects. Recently, mitragynine has been shown to exert conditioned place preference (CPP), indicating the rewarding and motivational properties of M. speciosa. Here, the involvement of GABAB receptors in mediating mitragynine reward is studied using a CPP paradigm in rats. First, we examined the effects of GABAB receptor agonist baclofen (1.25, 2.5 and 5 mg/kg) on the acquisition of mitragynine (10 mg/kg)-induced CPP. Second, the involvement of GABAB receptors in the expression of mitragynine-induced CPP was tested. We found that the acquisition of mitragynine-induced CPP could be blocked by higher doses (2.5 and 5 mg/kg) of baclofen. Baclofen at a high dose inhibited locomotor activity and caused a CPP. Furthermore, we found that baclofen (2.5 and 5 mg/kg) also blocked the expression of mitragynine-induced CPP. These findings suggest that both, the acquisition and expression of mitragynine's reinforcing properties is controlled by the GABAB receptor.
EVALuna2:211708